CO2 methanation over a Ni based ordered mesoporous catalyst for the production of synthetic natural gas. Issue 34 (21st March 2016) - Xu, Leilei; Wang, Fagen; Chen, Mindong; Zhang, Jian; Yuan, Kaidi; Wang, Liangjun; Wu, Kai; Xu, Guoqin; Chen, Wei
Abstract : A Ni based ordered mesoporous catalyst with excellent structural properties and thermal stability promised enhanced catalytic performance toward CO2 methanation. Abstract : Ni based catalysts have been considered as ideal candidates for the CO2 methanation reaction to generate synthetic natural gas owing to its high activity and low cost. In the present manuscript, we described a kind of ordered mesoporous NiO–Al2 O3 composite metal oxide, fabricated by a one-step evaporation induced self-assembly (EISA) strategy, which was utilized as the catalyst for CO2 methanation. The obtained material was characterized by XRD, N2 adsorption–desorption, TEM-EDS, H2 -TPR, and XPS techniques. The mesoporous catalyst with a large specific surface area (232.8 m 2 g −1 ), big pore volume (0.43 cm 3 g −1 ), tunable pore diameter (9.5 nm), strong metal–mesoporous framework interaction, and outstanding thermal stability (up to 800 °C) had a better catalytic performance than traditional non-mesoporous and supported reference catalysts. The ordered interconnected mesoporous network was beneficial to the mass diffusion of the gaseous reactants and enhanced the catalytic performance by providing sufficient accessible metallic active centers for the gaseous reactants. Besides, the Ni metallic nanoparticles could be stabilized via the space confinement effect of the mesoporous framework, finally reinforcing the catalytic stability. Generally, the presently reported ordered mesoporous NiO–Al2 O3 composite oxide promises to be a potential catalyst candidate for CO2 methanation.